Formação empreendedora da faculdade Atual da Amazônia e sua contribuição para o setor produtivo de Boa Vista/Roraima no período de 2008 a 2014 - Raskopf, Karla Rosane (2016)
The social and economic situation of Roraima is currently a important topic for discussion regarding its future and potential for the development of the state that since is origin, with the Constitution of 1988, has in the Federal Government’s fund transferring its main income resource and in the public administration one of its main sources of employment. In this context, this paper aims to show the contribution of workers with entrepreneur capacities graduated in the Faculdade Atual da Amazônia, and their role in the strengthening of the productive sector of Boa Vista from 2007 to 2014 as one of the factors for the economic transformations in the state of Roraima. The methodology used was the analytical and descriptive with a quali-quatitative approach. As for the technical procedures, it was bibliographic, documental and field research, making use of semi-structured questionnaires as the data collecting tool. The methods and techniques used have the purpose of contributing to the description of context and understanding of the aims. The relevance of this paper is regarding the presentation of significant data to the scientific community and to organizations, that will make possible a better understanding of the importance of these workers in the social and economic development of the state of Roraima, with professionals capable of acting in the local market and developing it in a sustainable way. Therefore, the institutions of higher education need to be aware of their local economic reality, matching their teaching plans to proper entrepreneur learning, supplying a school curriculum that has in its structure specific and general subjects that approach this topic, but also extracurricular activities that encourage students’ engagement in entrepreneurship through the contact with the local market and the adequate academic environment. In this perspective, it was confirmed that Faculdade Atual da Amazônia offered an environment intended to encourage entrepreneurship, aiming the development of attitudes and behavioral characteristics of leadership in order to have people making the difference in this scenario, forming professionals with an entrepreneur’s profile and acting in Boa Vista’s commerce, causing transformations in this productive sector in the capital, and therefore, contributing to the states’ economy.